Linguistic structure of dentistry thesis titles in spanish - Morales, Oscar Alberto; Perdomo, Bexi; Cassany, Daniel; Tovar, Rosa María; Izarra, Élix (Lenguas Modernas, 2021)
Titles play a fundamental role in the academic discourse. Studies on scientific article titles in English predominate. However, to date no studies on thesis titles in dentistry has been reported. We analyzed the discourse structure of 200 thesis titles defended in 2000-2019, and available on the web. In the analysis we examine qualitatively and quantitatively: length, punctuation, lexical grammatical structure and internal rhetorical combinations of the titles. An average of 19 words was found. Four types of titles were identified: nominal (86%), compound (12.5 %), prepositional (0.5 %), non-personal verbal (0.5 %), and complete sentence titles (0.5 %). Four rhetorical combinations of the title components were obtained: topicmethod; topic-method; topic-scope; and topic-description. Nominal constructions predominate using prepositional phrases (97 %), adjectives (30 %), non-personal verbal phrases (25 %), and relative clauses (5 %) as postmodifiers. Results provide useful information for teaching the writing process of thesis titles in dentistry.